2015
DOI: 10.1039/c4sc03991b
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective cis-β-lactam synthesis by intramolecular C–H functionalization from enoldiazoacetamides and derivative donor–acceptor cyclopropenes

Abstract: β-Lactam derivatives are produced through donor–acceptor cyclopropene intermediates in high yield with exclusive cis-diastereoselectivity, and high enantiocontrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…167,168 In these [1+ n ]-cycloaddition processes ( n = 2, 6), catalytically generated metallo-enolcarbenes served as one-carbon synthons (the carbene carbon) to furnish the corresponding cyclopropane, 158–165 cyclopropene, 166 and cycloheptatriene 167,168 derivatives.…”
Section: Mecc Reactions Of Enoldiazo Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…167,168 In these [1+ n ]-cycloaddition processes ( n = 2, 6), catalytically generated metallo-enolcarbenes served as one-carbon synthons (the carbene carbon) to furnish the corresponding cyclopropane, 158–165 cyclopropene, 166 and cycloheptatriene 167,168 derivatives.…”
Section: Mecc Reactions Of Enoldiazo Compoundsmentioning
confidence: 99%
“…102,122,132,152,167,168 Furthermore, the cyclopropenes, preformed from enoldiazo compounds under catalytic or thermal conditions, have proven to be effective metallo-enolcarbene precursors in several MECC reactions. 102,115,122,124,132,165,167,168 As depicted in Scheme 35, catalyst-controlled divergent outcomes are obtained from cycloaddition reactions of enoldiazoacetate 1a with Isoquinolinium methylide 40a . 132 Coordination of the Lewis basic methylide to the carbene-bound dirhodium catalyst promotes the formation of donor–acceptor cyclopropene from rhodium-enolcarbene.…”
Section: Catalyst-controlled Switchable Chemoselectivitymentioning
confidence: 99%
“…Donor‐acceptor cyclopropenes, constructed with an electron donating group (e.g., trialkylsilyloxy) at C1 and an electron withdrawing group (e.g., COR) at C2, are drawing increasing interest in organic synthesis owing to their versatile reactivity and convenient accessibility . They have been identified as the first‐formed intermediates in reactions of enoldiazoacetates, and they have been shown to undergo classic metal carbene reactions under very mild conditions . Formed by intramolecular cycloaddition of their precursor vinylcarbene intermediate, these donor‐acceptor cyclopropenes appear to be the carbene resting state for many, if not all, catalytic reactions of enoldiazoacetates and enoldiazoacetamides.…”
Section: Donor‐acceptor Cyclopropenes In Metal Carbene Transformationsmentioning
confidence: 99%
“…Recently, our group has discovered and reported that donor‐acceptor cyclopropenes generated from enoldiazo compounds are versatile carbene precursors. The catalytically generated metallo‐enolcarbenes from enoldiazo compounds have been effectively employed for dirhodium(II) catalyzed C−H insertion and cyclopropanation reactions, which are characteristic of metal carbene intermediates. In addition, the electrophilic center of the metallo‐enolcarbene intermediate that is delocalized to the vinylogous carbon makes this vinylcarbenic structure a metallo‐1,3‐dipole equivalent, which allows capture of a dipolar species in a stepwise or concerted process to complete formal [3+3]‐cycloaddition reactions ,.…”
Section: Donor‐acceptor Cyclopropenes In Metal Carbene Transformationsmentioning
confidence: 99%
“…In 1993, Hashimoto, Ikegami and co-workers first reported their famous complex, Rh 2 (S-PTTL) 4 [76,77], as a catalyst that manifested (along with its variants) high enantioselectivity levels in wide range of organic transformations [2,54,[78][79][80][81][82][83][84]. For example, in enantioselective [2,3]-sigmatropic rearrangement of the cyclic propargylic oxonium ylide shown in Scheme 5a, Rh 2 (S-PTTL) 4 provided the best enantioselectivity of 79% ee of the corresponding allenic bearing benzofuran-3-one product (Scheme 5a) [85].…”
Section: Global Catalyst Symmetrymentioning
confidence: 99%